Anesthetic Management in Cerebellopontine Angle Tumor (CPA) Removal Patients - Adelia Handoko; Taufiq Gemawan; Rizal Hadi Pratama; Renaldi Wibisono (Syntax Corporation Indonesia, 2023)
Introduction : Cerebellopontine Angle Tumor (CPA) is the most common type of tumor found in the posterior fossa. Without a proper anesthetic approach, this can increase the risk of brain edema and hemorrhage due to surgical manipulation. Case Illustration : A 46-year-old woman was diagnosed with a meningioma type CPA tumor, CT-Scan found meningioma in the left petrous tentorial tubercullum sellae with perifocal edema in the pons and left cerebellum. The patient was planned to get tumor excision surgery in a supine position. General anesthesia was performed, induced using propofol, fentanyl and rocuronium. The patient had a good hemodynamic profile while in the ICU postopertively. Discussion : Proper patient positioning during CPA tumor surgery is one of the important factors in the success or failure of the procedure. TIVA technique uses propofol and fentanyl, can reduce CBF reduce intracranial pressure, maintain brain perfusion pressure and reduce CMRO2 to protect brain tissue from damage.Conclusion : Several things that must be evaluated routinely in these patients are maintaining hemodynamic stability by maintaining adequate cerebral perfusion pressure, reducing cerebral blood flow, maintaining normal autoregulation, reducing the rate of cerebral metabolic oxygen, and maintaining an adequate cerebral oxygen supply.